1998
DOI: 10.1183/09031936.98.12010165
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator delivery by metered-dose inhaler in mechanically ventilated COPD patients: influence of end-inspiratory pause

Abstract: The delivery of bronchodilators with metered-dose inhalers (MDI) in mechanically ventilated patients has received considerable interest in recent years [1][2][3][4][5]. It has been shown that MDI adapted to the inspiratory line of the ventilator using a spacer device are as effective as nebulizers, despite a significantly lower dose of bronchodilator given by the MDI [1][2][3][4][5]. A spacer device is thought to be fundamental in order to demonstrate the efficacy of the bronchodilatory therapy given by MDI [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 19 publications
8
35
0
7
Order By: Relevance
“…It was further shown that the response was evident even when salbutamol was given in relatively low doses and not influenced by the inspiratory flow/time profile during drug delivery. Independent of the dose of salbutamol, DR remained relatively constant throughout the study, indicating that salbutamol acted by dilating the central airways, in line with previous observations [3,13,14]. Although expiratory resistance was not measured in the present study, it was most probably decreased by salbutamol, as indicated by the significant reduction in PEEPi and end-inspiratory static plateau pressure, indirect indices of dynamic hyperinflation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It was further shown that the response was evident even when salbutamol was given in relatively low doses and not influenced by the inspiratory flow/time profile during drug delivery. Independent of the dose of salbutamol, DR remained relatively constant throughout the study, indicating that salbutamol acted by dilating the central airways, in line with previous observations [3,13,14]. Although expiratory resistance was not measured in the present study, it was most probably decreased by salbutamol, as indicated by the significant reduction in PEEPi and end-inspiratory static plateau pressure, indirect indices of dynamic hyperinflation.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that salbutamol, against a background of relatively low airway resistance, was not able to reduce Rint further. A similar observation has been made previously [13].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1 The effect of bronchodilators in mechanically ventilated patients is commonly evaluated by the decrease in end-inspiratory airway resistance and in intrinsic PEEP. [2][3][4] End-inspiratory airway resistance and intrinsic PEEP are easily measured at the bedside in ventilated patients, without spontaneous respiratory efforts, with end-inspiratory and end-expiratory occlusions. 5 It is important to recognize however, that inspiratory and expiratory resistance differ, and it is the expiratory resistance that affects the development of dynamic hyperinflation.…”
Section: Introductionmentioning
confidence: 99%